The Study of the Relationship between Knowing and Politics through Rereading of Relationship between Physis and Logos in Aristotle`s Philosophy - behnam fooladi; Saeid Binayemotlagh; Yoosef Shaghool (حکمت و فلسفه, 2016)
Undoubtedly, “Physis” is one of the most prominent philosophical terms of Aristotle in the way that it can be seen as the basis for knowing from his point of view. Unfortunately, the neglect of some of Aristotle's teachings about the concept, has caused a lot of false judgment and perceptions about the philosopher. According to the author, one of the most important lessons is the close relationship of this concept with another key concepts of his philosophy, the “Logos”, forgetting that it was due to some of the contradictions and conflicts in the philosophy of Aristotle especially in the realm of knowledge. Detailed in this close relationship leads to another neglected doctrines of Aristotle's philosophy, the relationship of cognitive propositions and truth with political considerations. We shall show, by providing a reading of Aristotle's philosophy, which considers the relationships, that it can open the way for the elimination of some of the difficulties and conflicts that have been attributed to his thought. Therefore, in this study we examine the relationship between knowledge and Politics, through rereading relationship physis and logos in Aristotle's thinking.